Remodelling After Distal Forearm Fractures in Children II: The Final Orientation of the Distal and Proximal Epiphyseal Plates of the Radius - Friberg, K. S. I. (Acta orthopaedica, 1979)
In 39 children the steric orientation of both the distal and the proximal epiphyseal plates of the radius was evaluated 4 months to 10 years after distal forearm fractures that had healed with residual angulation. A residual fracture angulation was found to induce a change in orientation of both the distal and proximal epiphyseal plates. The final result of the reorientation was a normalization of the inclination of the plates in relation to the long axis of the bone. The proximal epiphyseal plate attained practically a normal orientation. The distal epiphyseal plate tended towards overcorrection. In two of the four cases with a primary angulation exceeding 20 degrees considerable normalization occurred, but a "normal" state was not reached. This indicates an upper limit for angulations permitting normalization of the orientation of the distal epiphyseal plate of the radius.